Practitioners of open dialogue report their personal transformations as a result of conducting network meetings - Taylor, Alita Kathryn; Taylor, Fletcher Brandon; Anderson, Deborah Ann (Frontiers in Psychology, 2023)
As health care providers practicing Open Dialogue, we cleave to the notion that the support we provide to users and their communities will lead to the kind of enduring personal transformation that they would consider an improvement. But what effects do Open Dialogue network meetings have towards instilling enduring personal transformations within the practitioners themselves? This subject is rarely addressed, particularly in academic settings. In this autoethnographic account, an experiencer/occupational therapist, a marriage & family therapist, and a psychiatrist each describe enduring transformations that they attribute to working together as Open Dialogue network meeting facilitators at one stand-alone clinic over two years. Our report illustrates the potential of Open Dialogue network meetings particularly the depth and breadth of transformation that can occur in all who attend them.